2020
DOI: 10.3390/cancers12040827
|View full text |Cite
|
Sign up to set email alerts
|

xCT Inhibition Increases Sensitivity to Vorinostat in a ROS-Dependent Manner

Abstract: As histone deacetylase inhibitors (HDACIs) have limited efficacy against solid tumors, we investigated whether and how oxidative stress is involved in sensitivity to HDACIs to develop a novel therapeutic option of HDACIs treatment. We first tested whether a reduction of the antioxidant glutathione (GSH) by glutamine deprivation affects sensitivity to a commercially available HDACI vorinostat and reactive oxygen species (ROS) accumulation. Next we investigated the relationship between a glutamate-cystine transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 51 publications
(62 reference statements)
3
20
0
Order By: Relevance
“…SLC7A11 has been reported to induce selective drug resistance [ 15 , 16 , 17 , 44 ]. Recently, SLC7A11 was also reported to be involved in the sensitivity to the histone deacetylase inhibitors [ 45 ]; thus, the pharmacological blockade of SLC7A11 not only inhibits tumor growth, but also reverses resistance to certain drugs. In the present study, we observed that the high expression of GLS was positively or negatively correlated with resistance to specific drugs.…”
Section: Discussionmentioning
confidence: 99%
“…SLC7A11 has been reported to induce selective drug resistance [ 15 , 16 , 17 , 44 ]. Recently, SLC7A11 was also reported to be involved in the sensitivity to the histone deacetylase inhibitors [ 45 ]; thus, the pharmacological blockade of SLC7A11 not only inhibits tumor growth, but also reverses resistance to certain drugs. In the present study, we observed that the high expression of GLS was positively or negatively correlated with resistance to specific drugs.…”
Section: Discussionmentioning
confidence: 99%
“…therapeutic success rate through inhibition of the tumour resistance mechanism. The rationales of therapeutic combinations with HDAC inhibitors have been discussed, mainly including combined DNAdamaging chemotherapeutic agents, radiotherapy, hormonal therapies, DNA methyltransferase inhibitors, and immunotherapies, as well as various other small-molecule inhibitors [39,40,[55][56][57][58].…”
Section: Combined Targeted Therapy With Hdacismentioning
confidence: 99%
“…Protein isolation was performed as previously described [ 41 ]. Briefly, cells were lysed with lysis buffer containing 50 mM Tris-HCl, 1% SDS, 1 mM dithiothreitol (DTT), and 0.43 mM 4-(2-Aminoethyl) benzenesulfonyl fluoride hydrochloride (ABSF).…”
Section: Methodsmentioning
confidence: 99%